Unlocking the potential of beta sitosterol: Augmenting the suppression of oral cancer cells through extrinsic and intrinsic signalling mechanisms - Selvaraj Jayaraman; Sathan Raj Natarajan; Bhuvaneswari Ponnusamy; Vishnu Priya Veeraraghavan; Sharmila Jasmine (Elsevier, 2023)
The global increase in the prevalence of oral neoplasms and related deaths can be attributed to social development and lifestyle factors, leading to poor prognosis and a lack of early clinical detection. Oral cancer ranks ranked sixth mostly diagnosed cancer and is a leading cause of cancer-related deaths. In light of these circumstances, our objective was to assess the potential of β-sitosterol, a naturally occurring herbal compound, as an anticancer agent against KB cells, a representative cell line for oral cancer. Our study primarily focused on evaluating the cytotoxic effect and mRNA expression of apoptotic proteins by β-sitosterol on KB cells. The results demonstrated a remarkable cytotoxic effect, leading to cell death. Further investigation using flow cytometric analysis revealed that this cell death was mediated through the initiation of the apoptotic signalling by β-sitosterol. The use of the bioinformatic tool, STITCH, supported our study by predicting drug-protein interactions and suggesting that β-sitosterol may play a significant role in targeting apoptotic pathways. Additionally, docking results were employed to validate the findings demonstrating high binding affinity of β-sitosterol with apoptotic-mediated signalling targets. To gain deeper insights into the molecular insights, we measured mRNA levels for BAX, BCL-2, MCL-1, P53, P21, MDM2, caspase3, and caspase9. Based on our comprehensive findings, our study concludes that β-sitosterol holds significant therapeutic potential against oral cancer cells. These results strongly suggest that this herbal compound should be further explored as a potential treatment option for oral cancer for clinical trial.